2019
DOI: 10.1177/0958305x19880878
|View full text |Cite
|
Sign up to set email alerts
|

Characterization analysis of activated carbon derived from the carbonization process of plane tree (Platanus orientalis) seeds

Abstract: In this work, plane tree seed-based activated carbons were characterized in detail for a variety of applications. The particularly important area of application would be in the artificial photosynthesis. After carbonization process of biomass precursor at 650°C, the resulting preliminary activated carbons were activated at various temperatures. The activated carbons were characterized by oxygen functionalities (a particularly important role has ester oxygen groups) which provide a unique microstructure. The ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The study by Janković et al, 2018 [ 7 ] aimed to examine a potential solid sorbent for a sorption process for harmful gases like CO 2 ; the purpose of the study was to choose experimental techniques for the characterization analysis of raw and pyrolyzed samples of plane tree ( Platanus orientalis L.) seeds and to assess the results. A study by Dodevski et al, 2020 was reported to characterize and analyze the activated carbons produced by the horizontal tubular reactor-based pyrolysis of plane tree seeds [ 8 ]. As they stated, since woody-based biomass and wood charcoals can also be used for cadmium adsorption, their research is significant.…”
Section: Introductionmentioning
confidence: 99%
“…The study by Janković et al, 2018 [ 7 ] aimed to examine a potential solid sorbent for a sorption process for harmful gases like CO 2 ; the purpose of the study was to choose experimental techniques for the characterization analysis of raw and pyrolyzed samples of plane tree ( Platanus orientalis L.) seeds and to assess the results. A study by Dodevski et al, 2020 was reported to characterize and analyze the activated carbons produced by the horizontal tubular reactor-based pyrolysis of plane tree seeds [ 8 ]. As they stated, since woody-based biomass and wood charcoals can also be used for cadmium adsorption, their research is significant.…”
Section: Introductionmentioning
confidence: 99%
“…Peak D indicates that the samples have amorphous C atoms with structural defects, which represents the characteristic peak of disordered carbon; peak G indicates that the C atom SP 2 of the sample is hybridized and represents the characteristic peak of ordered graphite structure. 36,37 The increase in the BAC peak intensity ratio ( I D / I G ) indicated that the aromatic structure with high stability increased; the activation process of KOH increased the structural defects of the activated carbon and deformed its carbon layer, which can effectively transport ions and improve the adsorption performance of the activated carbon. 38…”
Section: Resultsmentioning
confidence: 99%
“…This is expected to play a major role in bringing up the packing density, thus reflecting in power density. According to Tuinstra and Koenig Law, the I D /I G ratio is inversely proportional to the cluster diameter or size of the cluster (L a ) [36]. The relation between cluster size and I D /I G is given below:…”
Section: Raman Analysismentioning
confidence: 99%